Penerapan Model Pembelajaran Kooperatif Tipe Talking Stick untuk Meningkatkan Motivasi Belajar dan Hasil Belajar IPS (Sejarah) Siswa Kelas VII 6 SMP NEGERI 7 Denpasar - Rulianto Rulianto; Ida Bagus Nyoman Wartha (SINDANG: Jurnal Pendidikan Sejarah dan Kajian Sejarah, 2020)
According to the results of the observations were carried out research through observation of classes and interviews with teachers eye subjects IPS Class VII 6 in SMP State 7 Denpasar at half of odd year lesson 2018/2019 at the time of executing PPL ( practical experience of the field ) shows that the achievement of the results of study eyes lessons IPS less optimal. Based on the background behind what has been described in the above , it can be formulated the problem as follows : 1 ). How does the model of learning cooperative type of talking stick can increase the motivation to learn social studies students grade VII 6 SMP State 7 Denpasar? 2 ) . How does the model of learning cooperative type of talking stick can improve the outcomes of learning IPS students grade VII 6 SMP state 7 Denpasar ? . The objectives of this study are : 1 ). To find out the application of the cooperative learning model the talking stick type can increase social studies learning motivation in students of class VII 6 of SMP State 7 Denpasar. 2 ). To determine the application of the model of learning cooperative type of talking sick can improve the outcomes of learning IPS on students to weld VII 6 SMP State 7 Denpasar. Type of research this is the Research Action Class (PTK). research action class is compose. Based on the results d of two cycles that each cycle includes planning , implementation of action , observation and reflection . The method that is used in research this is the application of the model estab be disable in cooperative type of talking stick of study show motivation to learn the students can be seen in Cycle I obtained the category of motivation to learn ' high ' as many as 10 students and the category of ' quite high ' 14 students , while the category of ' low ' 16 students . In Cycle II there was an increase in the ' very high ' category of 7 students , the ' high ' category of 26 students , and the 'enough' category of 3 students . While the result of learning of students can be seen on cycle I that the value of the realm of cognitive students are on average 66 and completeness 72% and the realm of Affective values were obtained by the students is a very good 46.8%, good 46.8%, and quite a 36.0% while the sphere Psychomotor very good 50.4%, good 50.4% and sufficient 28%. In Cycle II domain of cognitive students are on average 78 and the thoroughness of 100, the realm of affective value that is obtained by the students is very good 90%, both 39.6% while psychomotor very good 90%, good 39.6%. Thus , can be concluded that the application of the model of learning cooperative type of talking stick can increase the motivation to learn and the results of learning IPS students grade VII 6 SMP Negeri 7 Denpasar, because through interaction are both between teachers and students as well as the atmosphere of learning that is fun facilitate students to understand and learn materials lesson so that objectives are desired can be achieved.